2021
DOI: 10.3390/molecules26040841
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in Small-Molecule Ligands of Medicinal Relevance for Harnessing the Anticancer Potential of G-Quadruplexes

Abstract: G-quadruplexes, a family of tetraplex helical nucleic acid topologies, have emerged in recent years as novel targets, with untapped potential for anticancer research. Their potential stems from the fact that G-quadruplexes occur in functionally-important regions of the human genome, such as the telomere tandem sequences, several proto-oncogene promoters, other regulatory regions and sequences of DNA (e.g. rDNA), as well as in mRNAs encoding for proteins with roles in tumorigenesis. Modulation of G-quadruplexes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 181 publications
0
43
0
Order By: Relevance
“…In the present review we have provided, without demanding completeness, a brief overlook on the potential of G4 ligands as therapeutic agents in cancer ( Table 1 ). In particular, we draw the readers’ attention to few examples that have been paradigmatic to depict how small molecule-mediated stabilization of G4 structures may represent an intriguing strategy that could be implemented in the fight of cancer [ 14 , 15 , 16 , 17 , 18 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the present review we have provided, without demanding completeness, a brief overlook on the potential of G4 ligands as therapeutic agents in cancer ( Table 1 ). In particular, we draw the readers’ attention to few examples that have been paradigmatic to depict how small molecule-mediated stabilization of G4 structures may represent an intriguing strategy that could be implemented in the fight of cancer [ 14 , 15 , 16 , 17 , 18 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The variety of small molecules evaluated for their G4 stabilizing properties is countless [ 34 ]. Most of them have been reported to exert a remarkable antiproliferative activity accompanied, in some cases, by evidence of pharmacodynamic activity, when used as single agents in several in vitro models of human cancers [ 2 , 12 , 14 , 15 , 16 , 17 , 18 , 29 , 57 , 63 ]. Moreover, synergistic pharmacological interactions have been also documented for some G4 ligands when combined to conventional anticancer therapies [ 12 , 14 ], both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intensive studies have revealed the formation of G-quadruplexes in vivo [ 20 , 21 , 22 , 23 ] and have provided evidence of their role in several key cellular processes, including gene transcription, chromatin epigenetics and DNA recombination. On the other hand, the linkage of G-quadruplex forming sequences with cancer diseases contributed to the rapid development of research focused on finding ligands, which can induce, stabilize or disrupt the G4 structure [ 24 , 25 , 26 , 27 ]. Since 2013, there has been a database containing the ligands tested against G-quadruplexes [ 28 ].…”
Section: Introductionmentioning
confidence: 99%